Nitrogen leaching losses and balances in conventional and organic farming systems in Kenya - Musyoka, M.W.; Adamtey, N.; Muriuki, A.W.; Bautze, D.; Karanja, E.N.; Mucheru-Muna, M.; Fiaboe, K.K.M.; Cadisch, Georg (Springer, 2019)
Organic farming has been proposed as a solution to foster agricultural sustainability and mitigate the negative environmental impacts of conventional farming. This study assessed N losses and soil surface N balances in conventional and organic farming systems in a sub-humid and semi-humid (Chuka and Thika) sites in Kenya. Nitrate–N (NO3−–N) leached was trapped at 1 m depth using the Self Integrating Accumulator core method and the changes in mineral-N were assessed at different soil depths and different crop growth stages. Both conventional and organic farming systems lost substantial amounts of NO3−–N at the early growth stages of all the crops. Cumulative NO3−–N leached was similar in all the farming systems in each cropping season. More NO3−–N was leached during potato cropping (22–38 kg N ha−1) than during maize (0.9–5.7 kg N ha−1) and vegetable cropping (1.9–2.9 kg N ha−1). Under maize cultivation, three times more NO3−–N was leached at Chuka site than at Thika site. During the potato cropping, between 79 and 83% of the N applied in the low input systems was leached, compared to 10–20% in the high input systems. Only Org-High exhibited a positive soil surface N balance (797–1263 kg ha−1) over a whole rotation period at both sites. We recommend reducing N applications for potato in all farming systems and at the early growth stages for all the crops in order to reduce N loss to the environment. We also recommend increasing N application rates in the low input systems and to developing a model to guide application of organic inputs.